Implementasi Nilai Karakter Kedisiplinan Peserta Didik dalam Meningkatkan Proses Pembelajaran Pendidikan Agama Islam (PAI) di Kelas VIII SMP Islam Karawang - Rina Maelani; Tajuddin Noor; Taufik Mustofa (Peneliti.net, 2021)
Education Of character Discipline is an adherence to regulation that strictly applies diciplinariy as the order of research is intended for : (1). Knowing the concept of a character dicipline. (2). Knowing what is the learning process of islamic education. (3). Knowing how the Implementation of the character discipline of learners enchances the proses of islamic education in the eighth grade of islamic high school. The approach to this study involves a qualitative data aapproach obtained through interviews with the Curriculum teacher of the islamic religious education course and some students for the eighth grade of islamic high school. Results from research suggest that: (1). The education of Character discipline in the VIII Grade especially in the subject of islamic education is essential in the learning process. (2). The feedback of learners during the islamic educational learning process is very possitive, because how teachers communicate materials is easy to absorb. (3). The implementations of character education in the islamic religious learning process is already applied by teachers as an example before starting learning besides having to perform Dhuha Shalat first and reading the short eighth grade student’s section required to memorise Juz 30 as many as 5 to 10 verses a day